Eluviation and Leaching of Elements from Broken Fly-Ash-Based Porous Geopolymer - Peng Shi (MDPI AG, 2021)
The fly ash from powerplants used for coal mine end backfilling can effectively reduce the impact of ground fly ash accumulation on the environment. However, due to the long-term action of the overlying strata and groundwater, when the backfilling body is broken, heavy metals will also be leached, thus having an impact on the groundwater. Therefore, in this paper, the eluviation and leaching of elements from a broken fly-ash-based porous geopolymer is studied. The fly-ash-based geopolymer material was prepared to perform a dynamic eluviation and static leaching test, and it was found that the amount of Cu and Zn in the leachate was less abundant, whereas Pb was more abundant, but far less than the limit of the Class III groundwater quality standard. An acidic environment and a smaller solid–liquid ratio can promote the leaching of Cu and Zn, while the leaching of Pb is basically unaffected by the pH value. Moreover, the amount of Cu, Zn, and Pb in the lixivium increased with the increase in leaching time, and the amount of Cu and Zn in the lixivium was still low after 150 h of leaching, whereas the amount of Pb was high, approaching the limit value of the Class III groundwater quality standard, showing a tendency to increase after 100 h of leaching. A leaching orthogonal experiment was designed, and the results showed that the main order of each factor affecting the leaching of heavy metals from the fly-ash-based geopolymer was grain size > pH > solid–liquid ratio; thus, the leaching of heavy metals from fly-ash-based geopolymer can be controlled, which is significant with respect to the extensive use of fly-ash materials underground.